A Transforming Growth Factor β-Induced Smad3/Smad4 Complex Directly Activates Protein Kinase A - Zhang, Lizhi (American Society for Microbiology, 2004)
Transforming growth factor β (TGFβ) interacts with cell surface receptors to initiate a signaling cascade critical in regulating growth, differentiation, and development of many cell types. TGFβ signaling involves activation of Smad proteins which directly regulate target gene expression. Here we show that Smad proteins also regulate gene expression by using a previously unrecognized pathway involving direct interaction with protein kinase A (PKA). PKA has numerous effects on growth, differentiation, and apoptosis, and activation of PKA is generally initiated by increased cellular cyclic AMP (cAMP). However, we found that TGFβ activates PKA independent of increased cAMP, and our observations support the conclusion that there is formation of a complex between Smad proteins and the regulatory subunit of PKA, with release of the catalytic subunit from the PKA holoenzyme. We also found that the activation of PKA was required for TGFβ activation of CREB, induction of p21(Cip1), and inhibition of cell growth. Taken together, these data indicate an important and previously unrecognized interaction between the TGFβ and PKA signaling pathways.